Methodological issues in management research : advances, challenges and the way ahead - Subudhi, Rabi N.; Mishra, Sumita (Emerald Publishing Limited, 2019)
Using contemporary examples of business and management research, predominantly within the context of India, this book offers numerous tools and techniques which can be applied to a diverse range of needs in social science research. With contributions from subject-experts in the field of research methodology and teachers of research methodology courses in leading business schools and universities of India, the book covers the essentials of management research. Covering both qualitative and quantitative research, topics discussed include: literature reviews research designs qualitative and quantitative data analysis grounded theory research questionnaires, focus groups, and interviews hypothesis testing case study research emerging trends in research and some advanced analysis. Specially selected Research Cases provide examples of some typical management research topics, outlining the detailed stages of their respective research processes and the latest data analysis techniques using SPSS, AMOS and STRATA. This practical element emphasises the variety of research methods and when/how to use them, making this book a useful resource for researchers from various academic disciplines and professional backgrounds.